Liquid crystal photoalignment on As2S3 chalcogenide thin films. (16th January 2017) - Sheremet, N V; Sharpnack, L; Gelbaor-Kirzhner, M; Agra-Kooijman, D M; Chaudhary, A; Kumar, T A; Klebanov, M; Abdulhalim, I; Kumar, S; Reznikov, Yu A
Abstract: Recent studies of photoalignment of liquid crystals (LCs) on chalcogenide surfaces have a rich variety of mechanisms responsible for the photoalignment on these materials. Both chalcogenide surface-mediated and LC bulk-mediated photoalignment were observed. We report on investigation toward understanding the origin of the chalcogenide surface-mediated photoalignment. The contributions of light-induced optical and surface morphological anisotropy of the chalcogenide surface were studied. Light-induced optical anisotropy in the film was observed by polarization interferometry and the surface anisotropy was measured by high-resolution x-ray reflectivity. The data reveals the lack of a strong anisotropy in the surfaces' morphology after irradiation with polarized blue light. At the same time, an evident correlation between the anchoring energy and the quality of the photoalignment was observed. This allows us to conclude that the photoalignment of LCs on chalcogenide surfaces is mainly determined by a light-induced anisotropic distribution of the glass structural elements in the bulk and on the chalcogenide surface.